Edukasi Cuci Tangan Pakai Sabun melalui Pendekatan Asset-Based Community Development untuk Meningkatkan Pengetahuan Masyarakat di Desa Crabak, Ponorogo: Handwashing with Soap Education through an Asset-Based Community Development Approach to Improve Community Knowledge in Crabak Village, Ponorogo - Rindang Diannita; Ide Mafaza Sansayto; Mohammad Muslih; Zimam Amaly Alfawzy; Adha Nur Lintang; Farih Habibul Mu'thi; Muhammad Nurdin Al Kahfi; Ahmad Ma'ruf Muzaidin; Arrosit Arrosit (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Handwashing with soap (HWWS) is a simple yet effective preventive measure to reduce the transmission of infectious diseases, including diarrhea and acute respiratory infections. However, the implementation of proper handwashing practices at critical times remains limited in many rural communities. This community service program aimed to improve community knowledge and awareness regarding the importance of HWWS and the correct six-step handwashing technique. The activity was conducted in Crabak Village, Ponorogo Regency, in February 2026, involving 30 community participants. The program adopted the Asset-Based Community Development (ABCD) approach, which emphasizes the utilization of local community assets and potentials. The implementation consisted of four stages: inculturation, discovery, design, and definition, which were carried out through health education sessions, interactive discussions, and demonstrations of the six-step handwashing practice. Program evaluation was conducted using pre-test and post-test questionnaires to assess participants’ knowledge improvement. The results showed a significant increase in community knowledge, with the average score rising from 61% before the intervention to 89% after the activity. Participants also demonstrated high enthusiasm and active engagement throughout the program. These findings indicate that community asset-based health education is effective in improving public understanding of proper handwashing practices. Continuous community-based health promotion programs are necessary to ensure sustainable behavioral change toward clean and healthy living practices.